THE USE OF COGNITIVE BEHAVIOUR THERAPY AS A TREATMENT OF INTERNET ADDICTION DISORDER IN ADOLESCENTS: LITERATURE REVIEW - Lutfian; Rizanti, Ayunda Puteri; Chandra, Ilany Nandia (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2023)
ABSTRACT Background: Internet Addiction Disorder (IAD) is a condition of internet dependence that can hinder adolescent development, as many as 73% of teenagers experience gadget addiction and as much as 75% experience internet addiction. IAD can cause significant losses to teenagers, such as they will not control themselves, feeling restless, anxious, depressed and can impair their daily activities. This can harm their psych and psychology. Purpose: This article aims to analyze the effectiveness of Cognitive Behavior Therapy (CBT) on IAD treatment in adolescents. Method: The method used in writing this article was a literature review. Reports were obtained through search sites such as Proquest, Science Direct, and PubMed with a range of publication years 2015-2021. Nine main journals were used as references by the authors. Results: From the nine major journals, it was found that CBT was effective in treating and reducing the signs and symptoms of internet addiction in adolescents. After being given CBT intervention for 1-12 meetings, there was an improvement in neurotransmitters and imaging results in the brain. Furthermore, giving CBT can reduce the duration of gadget use, anxiety, depression, and impulsive behavior in adolescents with IAD. Conclusion: CBT can be used to treat and prevent IAD in adolescents by changing maladaptive behavior into adaptive ones. Individuals are taught to understand and monitor their thoughts to identify which triggers feelings and actions of internet addiction.